Water and American government : the Reclamation Bureau, national water policy, and the West, 1902-1935 - Pisani, Donald J. (University of California Press, 2002)
Donald Pisani's history of perhaps the boldest economic and social program ever undertaken in the United States, shows in fascinating detail how ambitious government programs fall prey to the power of local interest groups and the federal system of governance itself.